2014
DOI: 10.1111/prd.12041
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐assisted complete prostheses

Abstract: The current review was undertaken to obtain a better understanding of the knowledge base of implant-assisted complete dental prostheses (fixed and removable) in the treatment of the completely edentulous maxilla or mandible. Indications, advantages and disadvantages, complications and maintenance issues, as well as the cost-effectiveness of both treatments, are discussed to help clinicians in their therapeutic decision-making. In summary, when indicated and depending on the patients' needs, both removable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 94 publications
(150 reference statements)
2
22
0
Order By: Relevance
“…Our 10‐year findings may clarify or confound the issue, as they do not provide the robust long‐term surgical outcomes. However, our quantitative data are supported by previous qualitative data, hence conforming to the current recommendations . Our qualitative research on these participants who had the implant surgery and wore these maxillary three‐implant overdentures certainly did provide us with knowledge of their positive perceptions of the treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our 10‐year findings may clarify or confound the issue, as they do not provide the robust long‐term surgical outcomes. However, our quantitative data are supported by previous qualitative data, hence conforming to the current recommendations . Our qualitative research on these participants who had the implant surgery and wore these maxillary three‐implant overdentures certainly did provide us with knowledge of their positive perceptions of the treatment.…”
Section: Discussionsupporting
confidence: 86%
“…However, our quantitative data are supported by previous qualitative data, 31 hence conforming to the current recommendations. 73 Our qualitative research on these participants who had the implant surgery and wore these maxillary three-implant overdentures certainly did provide us with knowledge of their positive perceptions of the treatment. Sadowsky and colleagues 74 recently proposed that in applying the hierarchy of evidence by Sackett and colleagues, 75 the number of implants appropriate for maxillary implant overdentures ranges across levels 1A to 2C, with consensus statements at level 5.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to mandibular CD, maxillary CD induced fewer complaints from patients in this study, consistent with previous findings that have indicated maxillary prostheses to be much better tolerated (Thomason, Heydecke, Feine, & Ellis, 2007). This finding also underscores that maxillary IOD might not show significant advantages in terms of PROMs when compared to CD (De Bruyn, Raes, Matthys, & Cosyn, 2015;Emami, Michaud, Sallaleh, & Feine, 2014).…”
Section: <0001supporting
confidence: 91%
“…The treatment of the fully edentulous patient is discussed by Emami et al. , from the use of full‐mouth fixed rehabilitations to overdentures retained by two to four implants. This latter treatment option can offer excellent results with a satisfactory cost–benefit ratio.…”
Section: Indication/treatment Planningmentioning
confidence: 99%